Accuracy of the cardiopulmonary resuscitation registry in an emergency department. Issue 4 (5th July 2011) - Park, Hyun Soo; Jung, Sung Koo; Kim, Hee Chan
Abstract : Background: The cardiopulmonary resuscitation (CPR) registry has been documented for medical records and investigational purposes. Although the accuracy of the CPR registry is generally adequate, it is difficult to precisely describe CPR in emergency situations. Objectives: To evaluate the accuracy of the CPR registry in an emergency department (ED) and to determine whether closed-circuit television (CCTV) is useful for recording CPR events. Methods: To assess the accuracy of the CPR registry, CCTV clips of the room in which CPR was performed in the ED and the corresponding CPR registry were consecutively collected and reviewed. The contents of the registry, specifically the time interval between patient arrival and CPR procedures, were compared with those determined by the CCTV clips. Accuracy was defined as the frequency of accurately registered time intervals differing by <30 s. Results: In a university-based ED between May and November 2009, 46 CPRs were performed and 150 CPR time intervals were documented in the CPR registry. The level of CPR registry accuracy was 54% (81/150). Conclusions: The accuracy of the CPR registry was improved by the use of CCTV. These results indicate that more detailed CPR investigations could be performed with the addition of CCTV-based information to the CPR registry.